Comparative evaluation of nerve stimulator guided supraclavicular brachial plexus block with or without ultrasound: An observational study - Gayathri Ramesh; Deepali Thakur; Pranjali Kurhekar; Raghuraman M. Sethuraman (Journal of Krishna Institute of Medical Sciences University)
Background: Supraclavicular block is a popular technique for upper limb surgeries. It can be performed with landmark, nerve stimulator (NS), ultrasound (US) guidance or a combination of techniques. NS can be an invaluable tool even in low resource set up. There are limited studies to compare NS guided supraclavicular block with (dual technique; Group NS+US) and without (Group NS) US guidance. Although US is gaining popularity, its availability at all times can be limited. Whenever available, the combination of two technique can improve the success rate. Material and Methods: Thirty patients (n=30) were included each in group NS and NS+US in the study. Both groups received 30 ml of 1:1 mixture of 2% adrenalized lignocaine and 0.5% bupivacaine. Both techniques were assessed in terms of ease of block execution (block execution time, number of skin punctures and needle redirections), block success rates and patient satisfaction. Onset and duration of block as well as complications were noted. Results: Both the groups were comparable in terms of age, gender, and mean weight. The block execution times were comparable but the dual technique group had significantly lower number of skin punctures and needle redirections. Both groups had similar success rates. The dual technique group had significantly earlier onset of motor and sensory blockade. No statistically significant difference in the incidence of complications was noted. The dual technique group had better patient satisfaction. Conclusion: A successful supraclavicular block can be performed with NS with or without US safely. The combination of two techniques eases the block execution, hastens the onset and provides better patient satisfaction.